经济全球化和国家经济安全问题的深层次研究 = On the economic globalization and economic security - 曾宏 Zeng, Hong (2008)
This article starts with an introduction of glolalization inclnding it origin and it is followed by an analysis of its forms and features and historical meanings. As a further step, this article tries to draw a clearer picture of the economic security affairs in the process of globalization, and the different characters in different phases. Finally, this article corcludes with suggestions to uphoed china' s economic security through building new conscious of economic security, constructing precautionary system of economic security and making use of the power of technology and education.